Health care in the new millennium : - Morrison, J. Ian (Jossey-Bass Publishers, 2000)
Health Care in the New Millennium is written by futurist Ian Morrison-author of The Second Curve and Future Tense and one of our nation's foremost health care analysts.In this provocative book, Morrison gives health care executives, doctors, and nurses a guided tour of what's in store for health care in the coming years and explains